Isolation of Endophytic Fungi from Vitex trifolia L and Antagonism Test against Sclerotium rolfsii and pathogenic bacteria - Muhammad Hasan Basri; Lalu Zulkifli; Abdul Syukur (Jurnal Biologi Tropis, 2021)
Plant damage by pathogenic fungi is often found in plants, one of which is caused by Sclerotium rolfsii. Biological control strategy offers a promising alternative for managing disease in plants because they are environmental friendly compared to pesticides application. One of the biological control offered is by using endophytic fungi isolated from Vitex trivolia L. The aim of the study was to isolate, to identify macroscopic and microscopic endophytic fungi from Vitex trifolia L and to test their antagonism potency against the pathogenic fungus Sclerotium rolfsii in vitro. The isolation obtained 7 endophytic fungi isolates identified based on their genus characteristics, nsmely Periconia sp, Aspergillussp, DendrophomaÃÂ  sp, GeotrichumÃÂ  sp, AmpulliferinaÃÂ  sp, ChalaraÃÂ  sp, dan Bispora sp and 2 isolates have not been identified. The Antibacterial test of the fungi isolate on the 4 tested bacteria showed that of all the fungi isolate have low activity. The antagonism test using the direct opposition method with the PIRG formula, showed that the 3 isolates had high percentage of growth inhibition, in which ALJ1, BLJ5, and ALJ3 isolate has ÃÂ 85%, 90%, and 100% respectively. This potency could be used as biological agents on the pathogenic fungus Sclerotium rolfsii.